The association between APOE ε4, age and outcome after head injury: a prospective cohort study - G. M. Teasdale; Gordon Murray; James A. R. Nicoll (2005)
Previous preliminary studies have suggested that possession of the APOE ε4 allele is associated with a poor outcome after head injury. This study was designed to confirm and extend those observations in a larger study with examination of additional variables. We prospectively identified admissions to a Neurosurgical Unit for head injury, collected demographic and clinical data, determined APOE genotypes and obtained follow-up information at 6 months. A total of 1094 subjects were enrolled (age range: 0–93 years, mean 37 years). Outcome was assessed using the Glasgow Outcome Scale. There was no overall association between APOE genotype and outcome, with 36% of APOE ε4 carriers having an unfavourable outcome compared with 33% of non-carriers of APOE ε4. However, there was evidence of an interaction between age and APOE genotype on outcome (P = 0.007) such that possession of APOE ε4 reduced the prospect of a favourable outcome in children and young adults. The influence of APOE genotype in younger patients after head injury can be expressed as, at age <15 years, carriage of APOE ε4 being equivalent to ageing by 25 years. This finding is consistent with experimental data suggesting that the effect of APOE genotype on outcome after head injury may be expressed through the processes of repair and recovery.